Phospholipases a2 from Viperidae snakes: Differences in membranotropic activity between enzymatically active toxin and its inactive isoforms - Ghazaryan, Narine A. (2014)
artículo -- Universidad de Costa Rica, Instituto de Investigaciones Clodomiro Picado. 2015. Este documento es privado debido a limitaciones de derecho de autor.